Upstream therapy of reperfusion disorders of hemodynamics, rhythm and conduction in patients with acute myocardial infarction with diabetes mellitus and metabolic syndrome (second message) - M.I. Shved; I.O. Yastremska; R.M. Ovsiychuk; L.P. Martyniuk; O.A. Prokopovych; Ya.M. Kitsak (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. There is a lack of scientific data on the mechanisms of influence of type 2 diabetes mellitus (T2DM) and metabolic syndrome (MS) on the incidence of complications in patients with myocardial infarction; no effective methods of their correction have been developed. The purpose of the study was to evaluate the incidence of reperfusion complications and the effectiveness of upstream therapy in patients with acute myocardial infarction combined with T2DM and MS by including L-carnitine/L-arginine and dapagliflozin, a sodium-glucose cotransporter-2 (SGLT2) inhibitor, in the treatment program. Materials and methods. We examined 38 patients with acute ST-elevation myocardial infarction (STEMI) on the background of T2DM and MS (study group) and 38 patients with STEMI without T2DM and MS (control group). In addition to the use of general clinical methods, detailed laboratory and instrumental examinations were performed: biochemical blood tests, evaluation of glucose, insulin, HOMA-IR, lipidogram, coagulogram, creatine kinase-MB, troponin T, electrocardiography, transthoracic echocardiography and coronary angiography. The risk of in-hospital mortality was predicted by the GRACE score. All patients with STEMI underwent urgent coronary angiography with subsequent balloon angioplasty and the infarct-dependent internal carotid artery stenting, as well as standard drug therapy according to the Ministry of Health protocol and were additionally prescribed dapagliflozin 10 mg/day and 5 intravenous infusions of L-arginine-L-carnitine mixture (4.2 and 2.0 g, respectively) in 100 ml of solvent. Results. STEMI on the background of T2DM and MS is significantly more common in middle-aged men. The development of STEMI was associated with the presence of comorbid conditions: hypertension, T2DM and MS, chronic kidney disease, and combined risk factors for coronary heart disease. The severity of the patient’s clinical condition was due to congestive heart failure III–IV and the presence of life-threatening complications of the acute period of myocardial infarction such as ventricular arrhythmias (45.3 %), conduction disorders (23.8 %), pulmonary edema (17.3 %), and acute left ventricular aneurysm (13.3 %). Compensation of carbohydrate metabolism in patients with myocardial infarction combined with T2DM and MS using dapagliflozin was accompanied by a significant reduction in the incidence of life-threatening complications: the incidence of rhythm disturbances in patients of the study group decreased from 87.5 to 50.0 %, heart failure (Killip class II–III) — from 70.0 to 12.5 %, which was significant compared with the control group. The inclusion of parenteral arginine (4.2 g/day) and L-carnitine (2.0 g/day) in the protocol therapy program contributed to a decrease in postinfarction cardiac remodeling and an increase in ejection fraction by 7 %. In this situation, cytoprotective therapy against the background of treatment with the SGLT2 inhibitor dapagliflozin acts as a pathogenetic upstream therapy. Conclusions. In patients with STEMI combined with T2DM and MS, hyperglycemia, insulin resistance and severe abnormalities of morphological and functional parameters of the heart with its systolic-diastolic dysfunction are observed at baseline, which are triggers of the complicated course of this pathology, with the development of heart failure syndrome, rhythm and conduction disorders. The comprehensive treatment with the inclusion of L-carnitine and L-arginine against the background of using the SGLT2 inhibitor dapagliflozin as upstream therapy helps restore tissue sensitivity to insulin, improve carbohydrate metabolism, central cardiovascular hemodynamics that is accompanied by a significant reduction in the frequency and severity of acute left ventricular failure and life-threatening reperfusion arrhythmias.